The Influence of Financial Literacy, Social Capital, Financial Inclusion, and Communication Skills on the Reach of Financial Institutions and Their Impact on the Effectiveness of Ultra Micro Financing (Case Study of MSMEs in Subang Regency) - Fenny Damayanti Rusmana; Jaja Suteja; Atang Hermawan (International Journal of Economics, Management and Accounting (IJEMA), 2026)
This study aims to analyze the influence of financial literacy, social capital, financial inclusion, and communication skills on the reach of financial institutions and their impact on the effectiveness of ultra-micro financing. The research used a quantitative survey method through the distribution of questionnaires to MSMEs in Subang Regency. Data were analyzed using Structural Equation Modeling (SEM). The results showed that financial literacy, social capital, financial inclusion, and communication skills simultaneously influence the reach of financial institutions. Partially, financial literacy and social capital do not influence the reach of financial institutions, while financial inclusion and communication skills do. Furthermore, this study found that the reach of financial institutions influences the effectiveness of ultra-micro financing. These findings provide insights for financing program managers and policymakers to improve program effectiveness by strengthening financial inclusion and the communication skills of MSMEs.